Kompensasi, Disiplin Kerja, dan Motivasi terhadap Kinerja Karyawan Bank Rakyat Indonesia Cabang Magetan - Olyn Seftani Haryanto; F.Anif Farida (Lembaga Penelitian Universitas YARSI, 2023)
Competitiveness in a company does not escape the performance of the most successful employees in the banking world. Employee performance can be measured from employees who have optimal motivation and work discipline and have high integrity within the scope of the company, employees or commonly called human resources are economic drivers and are also the main drivers in achieving the goals of a company. This study aims to test the effect of compensation, work discipline and work motivation on employee performance at Bank Rakyat Indonesia Magetan Branch. This study was conducted on 55 respondents, namely employees at Bank Rakyat Indonesia Magetan Branch using the probability sampling method. The research data was obtained by distributing questionnaires on compensation, work discipline, work motivation and employee performance directly to respondents. Researchers analyzed the data using SPSS 24 software. The analysis technique used is multiple linear regression. The results showed that partially compensation, work discipline and motivation had a positive and significant effect on employee performance.